A study on the issues and challenges of implementing ERP system - Bartolome, Meneses Consuelo (2008)
This project aims to provide better understanding of the issues faced by companies in adopting an ERP System Software through an in-depth case study as well as through previous empirical studies reported in literature. The case study identifies which factors are important.